Intellectual Capital as a Variable Intermediary between The Quality of Working Life and Methodology of Six Sigma Application to the Employees in the Ministry of Health in the Kingdom of Saudi Arabia - Eissawi, Nevin; Eltahan, Emad (The Arab Journal of Administration, 2018)
Knowledge is considered in recent years one of the most important organizational resources and is the basis for stable development, especially in highly competitive environments or that are exposed to constant changes environments. Many organizations that sink into the iceberg my knowledge is not final and there but in severe famine of knowledge so companies allocate a large share of spending for the sake of access to knowledge and new ways and methods. The problem with the search in an attempt to answer the main question: “To what extent contribute to the quality of working life in the intellectual capital development and application of the methodology of Six Sigma in the Ministry of Health of Saudi Arabia.» The goal of research is to identify the role of intellectual capital as a variable and mediator in the relationship between quality of life and functional methodology of Six Sigma application to workers in the Ministry of Health in the Kingdom of Saudi Arabia. And adopted a researcher on the descriptive method, which is based on the interpretation of the status quo of the phenomenon under study, research and determine the dimensions and conditions of the phenomenon, this next to an analysis and interpretation of the special phenomenon data, the researcher also used in the field study method of questionnaire through personal interviews and e-mail to employees. The researcher found the presence is a significant correlation between the quality of working life and all of the intellectual and methodological money Six Sigma within the Ministry of Health in Saudi Arabia, as well as there is a significant moral quality career impact on both the intellectual and methodological money Six Sigma within the Ministry of Health in Kingdom of Saudi Arabia. Finally, the researcher recommended the interest in providing health work, which works to achieve high accomplishments above normal for all functions within the Ministry of Health in Saudi Arabia climate, through attention to occupational safety and security standards.